Kopontren Strategy in Cultivating a Halal Lifestyle in Food at the Miftahul Ulum Women's Islamic Boarding School - Dini Durrotul Ummah (Department of Islamic Economics, Postgraduate Program, UIN Kiai Haji Achmad Siddiq, Indonesia, 2024)
The development of halal potential can be done optimally by introducing a group of Muslims who are in a joint settlement such as Islamic boarding schools. At the Miftahul Ulum Islamic boarding school there is a cooperative of Islamic boarding schools that have been established independently, Islamic boarding schools have great potential in developing a halal lifestyle because they have great human resource potential, plus because the pesantren is a center for Islamic studies. The purpose of this study is to find out the strategy of planning the halal lifestyle culture in food, the strategy of implementing the halal lifestyle in food, and the evaluation of halal lifestyle culture in the Al-ikhwan Miftahul Ulum Lumajang kopontren. This research is a qualitative research with a case study. Meanwhile, data collection was carried out by interview, observation, and documentation techniques. Furthermore, data analysis techniques are used, namely data collection, data reduction, data presentation, and conclusion drawn. The validity of the data is used by checking to extend the research period. The results of the study show that in the Al-ikhwan Miftahul Ulum Lumajang kopontren Al-ikhwan Lumajang has carried out strategic planning, implementation, and evaluation in cultivating a halal lifestyle in the food sector. With the regulation prohibiting buying food outside the pesantren and fulfilling the needs of the pesantren cooperative. In addition, the kopontren collaborates with the pesantren in providing an evaluation to students regarding the importance of consuming halal and clean food as a form of Muslim obedience to the creator.